Determinants of Poverty in The Provinces of Sumatra Island - Ramadhani, Hana Fitria; Rachmad R, Muhammad; Achmad, Erni (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: This study aims to analyze the determinants of poverty in the provinces of Sumatra for the period 2015–2024, focusing on the Human Development Index (HDI), unemployment rate, Provincial Minimum Wage (PMW), and economic growth, as well as formulating poverty alleviation strategies. The study is motivated by the persistent disparity in poverty levels among provinces, indicating uneven economic development. Background Problems: Poverty disparities across provinces in Sumatra indicate that economic development outcomes are not evenly distributed, despite the region’s significant contribution to the national economy. Research Methods: This study uses secondary panel data obtained from the Central Statistics Agency (BPS). The analysis employs panel data regression with the Random Effect Model (REM) and is complemented by Revealed Comparative Advantage (RCA) analysis for strategy formulation. Finding/Results: The results show that partially, the Human Development Index (HDI) has negative and significant effect on poverty, while the unemployment rate has a positive and significant effect. Meanwhile, the Provincial Minimum Wage (PMW) and economic growth do not significantly affect poverty, as indicated by probability values greater than 0.05. Conclusion: This study finds that poverty in Sumatra is primarily determined by human capital quality and labor market conditions. Human Development Index (HDI) has a significant negative effect on poverty, while unemployment has a significant positive effect. In contrast, economic growth and the provincial minimum wage (UMP) are not statistically significant, indicating that economic growth remains non-inclusive and does not directly reduce poverty.